European Union and China´s competition for environmental leadership : Case study of the African region - Novosad, Matěj; Lisa, Aleš, 1956-; Vymětal, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
In my thesis I examine the approaches and tools, which the European Union and the People´s Republic of China use to pursue environmental leadership in Kenya, and to what results. To answer my research questions, i conducted a qualitative content analysis of primary and secondary sources. The study shows that the EU Uses the attractiveness of the Single Market as an incentive, to achieve regulatory alignment. Producing tangible impacts on Kenya’s environmental institutions and policy frameworks. Whereas China by contrast, employs more of a development first approach centered around its BRI, achieving incredible results in infrastructural development, which generates rather mixed environmental outcomes
Vedoucí práce: Aleš Lisa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses